Balinese Art and Tourism Promotion: From the 1931 ‘Paris Colonial Exposition’ to the Contemporary ‘Paris Tropical Carnival’ - I Wayan Sukma Winarya Prabawa,; I Wayan Winaja, (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
The development of tourism in Bali cannot be separated from the role of artists and the community in preserving Balinese culture and tradition. This paper aims to analyze the role of artists in the preservation of Balinese culture that is associated with the promotion of Bali tourism in overseas through cultural performances which is currently known as marketing 3.0 models. Through research literatures, interviews to sample of participants and qualitative descriptive approach, this paper suggests that artists and society since the colonial era to the present day have taken an important role as tourism promotion ambassador of Bali and Indonesia, where the artists and the community have successfully presented the emotion or the spirit of Bali’s tourism a ractions.
Keywords: Balinese arts; tourism promotion; cultural tourism; marketing 3.0